Black Aliveness, or A Poetics of Being - Quashie, Kevin Everod (Book collections on Project MUSE., 2021)
"Kevin Quashie analyzes texts by of Lucille Clifton, June Jordan, Toni Morrison, Evie Shockley, Gwendolyn Brooks, and others to argue for a black aliveness that is disarticulated from antiblackness and which provides the basis for the imagination and creation of a black world."--